Methylene blue in anticancer photodynamic therapy: systematic review of preclinical studies - Taldaev, Amir; Terekhov, Roman; Nikitin, Ilya; Melnik, Elizaveta; Kuzina, Vera; Klochko, Mikhail; Reshetov, Igor; Shiryaev, Artem; Loschenov, Victor; Ramenskaya, Galina (Frontiers in Pharmacology, 2023)
Background: Methylene blue has a long history of clinical application. Thanks to phenothiazine chromophore, it has a potential in photodynamic anticancer therapy. In spite of growing body of literature that evaluated the action of this dye on different types of cancer, the systematic understanding of this problem is still lacking. So, this systematic review was performed to study efficacy of methylene blue in photodynamic anticancer therapy.Methods: This systematic review was carried out in accordance with the PRISMA guidelines, and the study protocol was registered in PROSPERO (CRD42022368738). Articles for the systematic review were identified through PubMed database. SYRCLE's risk of bias tool was used to assess the studies. The results of systematic analysis were presented as narrative synthesis.Results: Ten studies met the inclusion criteria and these full texts were reviewed. In the selected articles the dosage of dye infusion ranged from 0.04 mg/kg to 24.12 mg/kg. The effectiveness of photodynamic therapy with methylene blue against different types of cancer was confirmed by decrease of tumor sizes in 7 articles.The results of the systematic review supported suggestions that photodynamic therapy with methylene blue helps against different types of cancer, including colorectal tumor, carcinoma, and melanoma. In case of nanopharmaceutics use a considerable increase of anticancer therapy effectiveness is observed. The further research of methylene blue in photodynamic anticancer therapy is needed.